The Impact Of Using BBC 6 Minute English Podcast On Students’ Listening Comprehension - Rifai, Muhammad; Syafrizal, Syafrizal; Rima, Rosmania (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
In the context of English language learning, listening remains one of the most challenging skills for students to master. Many learners struggle to understand authentic spoken English because classroom listening activities often rely on monotonous, monologue-based audio materials. To address this issue, this research examines the effect of the BBC 6 Minute English podcast on students’ listening comprehension at SMAN 1 Cikande. This study employed a quasi-experimental design with a pretest–posttest control group involving 76 eleventh-grade students divided into experimental and control classes. Data was collected through pretests and posttests, and analyzed using SPSS version 26 with an independent samples t-test and effect size calculation. The results showed a significant difference between the two groups, with the experimental class showing higher improvement (pretest mean = 66.34, posttest mean = 84.11) compared to the control class (pretest mean = 69.95, posttest mean = 73.50). The significance value of 0.000 (p < 0.05) indicated a positive effect of podcast-based instruction, while the effect size (Cohen’s d = 1.03) demonstrated a large impact. These findings suggest that integrating the BBC 6 Minute English podcast into classroom learning effectively enhances students’ listening comprehension and motivation to engage with authentic English materials.